TINJAUAN MENGENAI ASPEK PERILAKU DALAM PENGGUNAAN TEKNOLOGI INFORMASI - -, Lamidi - (Universitas Slamet Riyadi, 2009)
ABSTRACT Usage of information technology at least have three important components, that are hardware, software and brainware. Research about usage of information technology which focused of behavior aspect more done. This thing very important because behavior aspect of brainware in articulating information technology to determine success of applying of information technology, so that behavior of user information technology of course important to be paid attention. Technology Acceptance Model (TAM) is modeling widest research and popular applied to adoption of information technology. The assumption of TAM that 2 individual confidence, that is perceived usefulness and perceived easy of use be main effect for behavior of computer acceptance. This article expected able to give references about the importance of readiness of user in development information technology, which